Philosophy and Engineering: An Emerging Agenda - Poel, Ibo.; Goldberg, David; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Whereas science, technology, and medicine have all called forth dedicated philosophical investigations, a fourth major contributor to the technoscientific world in which we all live - that is, engineering - has been accorded almost none of the philosophical attention it deserves. This volume thus offers a first characterisation of this important new field, by some of the primary philosophers and ethicists interested in engineering and leading engineers interested in philosophical reflections. The volume deals with such questions as: What is engineering? In what respect does engineering differ from science? What ethical problems does engineering raise? By what ethical principles are engineers guided? How do engineers themselves conceive of their profession? What do they see as the main philosophical challenges confronting them in the 21st century? The authors respond to these and other questions from philosophical and engineering view points and so illustrate how together they can meet the challenges and realize the opportunities present in the necessary encounters between philosophy and engineering - encounters that are ever more important in an increasingly engineered world and its problematic futures.
Philosophy -- Philosophy and Engineering: Setting the Stage -- Distinguishing Architects from Engineers: A Pilot Study in Differences Between Engineers and Other Technologists -- The Rise of Philosophy of Engineering in the East and the West -- Multiple Facets of Philosophy and Engineering -- Comparing Approaches to the Philosophy of Engineering: Including the Linguistic Philosophical Approach -- Focussing Philosophy of Engineering: Analyses of Technical Functions and Beyond -- Philosophy, Engineering, and the Sciences -- Engineering Science as a (3z(BDiscipline of the Particular(3y(B? Types of Generalization in Engineering Sciences -- How the Models of Engineering Tell the Truth -- Limits to Systems Engineering -- Ethics -- Integrity and the Ethical Responsibilities of Engineers -- Prioritising People: Outline of an Aspirational Engineering Ethic -- Ethical Principles for Engineers in a Global Environment -- Professional Ethics Without a Profession: A French View on Engineering Ethics -- Imagining Worlds: Responsible Engineering Under Conditions of Epistemic Opacity -- Transferring Responsibility Through Use Plans -- Design Problems and Ethics -- Ethics in Innovation: Cooperation and Tension -- Teaching Ethics to Engineering Students: From Clean Concepts to Dirty Tricks -- A Collaborative Platform for Experiments in Ethics and Technology -- Reflection -- Why Philosophy? Why Now? Engineering Responds to the Crisis of a Creative Era -- A World of Things Not Facts -- Architecting Engineering Systems -- Bits Don$1 (Bt Have Error Bars: Upward Conceptualization and Downward Approximation -- Metaphysics of Engineering -- Engineering Determinacy: The Exclusiveness of Technology and the Presence of the Indeterminate -- Quo Vadis, Humans? Engineering the Survival of the Human Species -- The Focal Engineering Experience.s
Keywords: Philosophy (General).; Ethics; Philosophy, modern; Science -- Philosophy; Technology -- Philosophy; Engineering; Engineering design; Philosophy; Philosophy of Technology; Engineering, general; Engineering Design; Modern Philosophy; Philosophy of Science; Ethics